2011
DOI: 10.1002/biot.201100459
|View full text |Cite
|
Sign up to set email alerts
|

The two faces of His‐tag: Immune response versus ease of protein purification

Abstract: Figure 1. While the use affinity tags is a convenient way to enhance protein purification, such modifications may have unanticipated immune effects. In the article by Kahn et al. [7], the authors show that adding polyhistidine tags to a potential malaria vaccine alters the immune response to the vaccine in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…5C and D indicate that all vaccines elicited a significantly higher Ab titer to the Histidine tag than those vaccines with a foreign epitope insertion N-terminal to the Histidine tag (HBcAg + SSM and mHBcAg + SSM), following the same pattern as the Ab titers to the whole DHBcAg protein. Together these data demonstrate that the histidine tag located at the N-terminus of the vaccine candidates may play a large role in Ab recognition to each protein, as has been seen previously by others, and the placement of an epitope N-terminal to the tag may reduce its immune interaction [40].…”
Section: Vector Protein Antibody Generationsupporting
confidence: 80%
“…5C and D indicate that all vaccines elicited a significantly higher Ab titer to the Histidine tag than those vaccines with a foreign epitope insertion N-terminal to the Histidine tag (HBcAg + SSM and mHBcAg + SSM), following the same pattern as the Ab titers to the whole DHBcAg protein. Together these data demonstrate that the histidine tag located at the N-terminus of the vaccine candidates may play a large role in Ab recognition to each protein, as has been seen previously by others, and the placement of an epitope N-terminal to the tag may reduce its immune interaction [40].…”
Section: Vector Protein Antibody Generationsupporting
confidence: 80%
“…The inclusion of a His‐tag downstream of the sortag allowed purification of the sdAb via IMAC during sdAb production, while it resulted in the loss of the His‐tag upon conjugation. The latter is a great advantage for clinical translation where the use of His‐tagged proteins is avoided since they increase the possible risk of immune responses . Of note, the safety profile of the use of SrtA‐mediated conjugation in clinical tracer production, and in particular the non‐immunogenic character of the sortag and absence of metal contaminants coming from the IMAC step in purification, still needs to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these studies have revealed that the tacn‐based IMAC resins exhibit significantly increased association constants and higher kinetic binding rates with recombinant proteins containing N‐terminal metal binding tags specifically designed for this purpose, such as the NT1A tag, compared with the [His]6 tag, whilst the efficiency of removal of tags specifically selected to be good substrates for DAP‐1 could be improved compared with [His]6 as a result of greater control over enzyme activation by attaining the optimal pH window for the cleavage conditions. Moreover, recent studies with recombinant malarial antigens have demonstrated (Khan et al ., ; Randolph, ) that a [His]6 tag can have significant humoral and cellular immunological consequences and have thus provided an additional driver for the development of alternative tags for use in IMAC purification of recombinant proteins.…”
Section: Discussionmentioning
confidence: 99%